2018
DOI: 10.3389/fmicb.2018.02000
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome of the Gastrointestinal Tract of a Range-Shifting Marine Herbivorous Fish

Abstract: Globally, marine species’ distributions are being modified due to rising ocean temperatures. Increasing evidence suggests a circum-global pattern of poleward extensions in the distributions of many tropical herbivorous species, including the ecologically important rabbitfish Siganus fuscescens. Adaptability of a species to such new environments may be heavily influenced by the composition of their gastrointestinal microbe fauna, which is fundamentally important to animal health. Siganus fuscescens thus provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 73 publications
6
79
0
Order By: Relevance
“…Differences in environment [46,52], season [48], age [36,50,51], sex [36], diet [18,42] or genetic background [53] can di cult comparisons among studies. In addition, technical differences, such as part of the intestine sampled [52,81], type of sample (adherent, transient or total microbiota) [82,83], DNA extraction techniques or analysis methodology [84,85], can also be a source of variation. However, even though we cannot make statistically sound comparisons among studies, it is safe to say that the typical microbial architecture of gilthead sea bream intestine was found in this study and the different genetic backgrounds of the families do not alter this core composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in environment [46,52], season [48], age [36,50,51], sex [36], diet [18,42] or genetic background [53] can di cult comparisons among studies. In addition, technical differences, such as part of the intestine sampled [52,81], type of sample (adherent, transient or total microbiota) [82,83], DNA extraction techniques or analysis methodology [84,85], can also be a source of variation. However, even though we cannot make statistically sound comparisons among studies, it is safe to say that the typical microbial architecture of gilthead sea bream intestine was found in this study and the different genetic backgrounds of the families do not alter this core composition.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were mainly focused on de ning baseline populations [35][36][37] or changes induced by diet [18,[38][39][40][41][42][43][44] or environmental conditions [45]. The microbiota is composed of very dynamic populations that are affected by different factors [18,36,[53][54][55]42,[46][47][48][49][50][51][52] such as diet, season, habitat, rearing density, age, sex and genetic background, the focus of the current study. There are not many studies de ning the effects of the host genome on intestinal microbiota composition in sh.…”
Section: Introductionmentioning
confidence: 99%
“…The facultative anaerobic bacterial classes Bacteroidia, Clostridia and Mollicutes were generally in higher abundance in the mid and posterior intestinal regions than the stomach. Differences in microbiomes along the intestinal tract have been recorded in the rabbit sh Siganus fuscescens [91], with midgut communities more representative of the environmental sources and hindguts hosting a microbiome more specialised to anaerobic conditions and fermentation [92]. The increase in Bacteroidia, Clostridia and Mollicutes along the intestines may be due some members of the class being mutualistic components of the sh gastrointestinal ora.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, many environmental and biological factors can affect the diversity and structure of microbiomes within the gastrointestinal (GI) tracts of sh [13]. Microbiomes in sh GI tracts are highly structured [14] with different parts housing very different microbial communities [15][16][17]. Fish ' rst feeding' is emerging as a critically important step in structuring their GI microbiomes throughout their lifespan [10].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesised that supplementation of diets with some of these seaweeds -particularly those with interesting bioactive compounds -at inclusion rates that are realistic in an industrial context, would lead to signi cant changes to the GI microbiomes in these sh. Recently, several other studies have characterised the GI microbiome of this species and revealed clear differences in microbial communities along the gut axis with more transient and food associated bacteria in the midgut compared to the hindgut, which harboured bacteria more likely to members of the host gut microbiome [15,17]. In addition to providing a useful baseline, these studies also provided us with an opportunity to compare hindgut microbiomes between distinct populations of the same sh species separated spatially (by thousands of kilometres) and temporally (11-20 months) and assess whether any particular experimental diets in uenced similarities between populations [15,17].…”
Section: Introductionmentioning
confidence: 99%